Diversifikasi Olahan Limbah Kulit Durian Sebagai Komoditas Produk Unggulan Desa Wisata Branjang Menuju Sustainable Independent Economic Revitalization - Zaenuri, Ahmad; Ranihusna, Desti; Brantas Abiprayu, Kris; virma, Made (Universitas Pahlawan Tuanku Tambusai, 2024)
Revitalizing a Sustainable Independent Economy through diversifying durian skin waste food in Branjang Village is a positive step. Durian, as a typical tropical fruit and a leading commodity in the Branjang Tourism Village, has economic potential that can be further optimized. To be able to develop superior products in the Branjang Tourism Village, this can be done by developing innovative processed products from durian skin waste so that the income obtained can encourage the economic independence of the Branjang Village community in a sustainable manner. Durian fruit farmers in Branjang Village have not been able to make maximum use of durian skin waste management which has the potential to bring in